QISKIT POCKET GUIDE quantum development with Qiskit - WEAVER, JAMES (O'REILLY MEDIA, 2023)
The quantum computing market is predicted to grow by nearly $1.3 billion over the next five years. Why? Given their quantum mechanical nature, quantum computers are expected to solve difficult problems in chemistry, optimization, finance, and machine learning that classical computers find impossible to unravel. This pocket guide provides software developers with a quick reference to Qiskit, an open source SDK for working with quantum computers. Packed with helpful programming examples, tables, figures, and lists, this handy book helps you find the information you need to develop and debug quantum programs. Whether you're focused on business, engineering, or scientific applications, you'll learn how to choose and apply appropriate Qiskit classes, methods, and functions. Learn how to create quantum circuits, define quantum gates, and leverage the transpiler Explore modules for implementing quantum information concepts and quantum algorithms Survey features of Qiskit that abstract and facilitate working with various quantum computers and simulators Learn how to use the latest version of the Open Quantum Assembly Language.